Development of Practical Wind-Assisted Ship Propulsion (WASP) Calculation for Fuel Consumption and Emission Reduction - Isna Aulia Marifa; Dian Purnama Sari; Wiwin Sulistyawati (Naval Architecture Department, Kalimantan Institut of Technology, 2026)
Integration of Wind-Assisted Ship Propulsion (WASP) serves as a strategic solution for the maritime industry to achieve Net Zero Emission by 2050. This research evaluated the interaction between sail design and route optimization for a 265 GT fishing vessel operating around Benoa, Bali to maximize fuel savings and emission reductions. Three hard sail profiles, arc-shaped, NACA 0012, and NACA 0015, were analyzed at operational speeds of 7 and 10 knots. An improved weather-routing framework based on the A* (A-star) algorithm* was developed, integrating weather forecasts, ship specifications, and force matrices to determine optimal navigational paths. Simulations conducted on routes around Benoa, Bali, demonstrated that the combination of aerodynamic wing sails and intelligent routing improved efficiency by 1.24% to 12.59%. The results confirmed that the synergy between WASP technology and precise pathfinding significantly reduced carbon footprints while enhancing the economic viability of shipping operations. These findings provide a scalable framework for sustainable maritime practices and for achieving global decarbonization targets.